Sunbringer ebook A novel. - Kaner, Hannah (Fallen Gods, 2024)
"Brilliant mythology-inspired world-building paves the foundation for Kaner's fantasy adventure, but it's the fully realized ensemble cast that, ultimately, makes the series so memorable."— Elle "An epic fantasy odyssey." — Entertainment Weekly Return to the world of Godkiller in this thrilling sequel to the #1 internationally bestselling fantasy debut When Middren falls to the gods, your kind will be the first to die. Gods are forbidden in the kingdom of Middren—but now they are stirring, whispering of war. Godkiller Kissen sacrificed herself to vanquish the fire god Hseth, who murdered her family and endangered her friends. But gods cannot be destroyed so easily, and Hseth's power threatens to reform with even greater strength and a thirst for vengeance. As tensions rise throughout the land, the kingdom needs its Godkiller more than ever. Still reeling from the loss of Kissen, young noble Inara and her little god of white lies, Skedi, have set out to discover more about the true nature of their bond. As the divide between gods and humans widens, Inara and Skedi will uncover secrets that could determine the fate of the war to come. Meanwhile, Elogast, no longer a loyal knight of King Arren, has been tasked with killing the man he once called friend. The king vowed to eradicate all gods throughout the land, but has now entered into an unholy pact with the most dangerous of them all. And where his heart once beat, a god now burns. . . " A richly rendered world . . . Kaner writes action that's both fun and intelligible." — The Washington Post